Endometriosis, Mental Health and Quality of Life - Theofilou, Paraskevi (Journal of Public Health International, 2024)
This article explores links between endometriosis, mental health, and quality of life. It reviews symptom burden, comorbidity patterns, and multidisciplinary care approaches.
Keywords: chronic pelvic pain; infertility; psychiatric symptoms; depression; anxiety disorders; mental stress